Bullying Perpetration and Homophobic Teasing: Mediation through Gender Role Attitudes - Yutong Gao; Zhenying Zhang; Binli Chen; Xiying Wang (Children, 2022)
Homophobic teasing or name-calling, one form of school-related gender-based violence, refers to the use of derogatory language or actions towards sexual- or gender-nonconforming individuals. Research in the Global North has indicated that it is highly prevalent among adolescents, and is associated with a broad range of negative outcomes for both victims and perpetrators. However, such behaviors remain understudied in China. Using a cross-sectional design, the present study investigated the structural relations between homophobic teasing, bullying perpetration, and gender role attitudes among 1915 Chinese high school students. The results showed that 11.5% of the participants had perpetrated such harassment in the past month. Structural equation analyses revealed that bullying perpetration predicted more teasing involvement, and that the relationship was partially mediated by gender role attitudes among both female and male youth. The moderation effect of sex was found only for the direct effect of bullying; such that males who engaged in bullying were more likely to perpetrate homophobic teasing than females. These findings suggest the need for further examination and effective interventions and preventions for the behavior in Chinese contexts.